Korelasi Antara Kehadiran Siswa dan Hasil Belajar Matematika SMA - Vrasetya, Arshinta; Nasution, Eline Yanty Putri (Universitas Cokroaminoto Palopo, 2025)
This study analyzes the relationship between student attendance and mathematics learning outcomes at SMA Negeri 4 Sungai Penuh using a quantitative approach with a correlational design. The sample consists of 30 tenth-grade students selected through purposive sampling. Attendance data and final exam scores were collected through documentation and analyzed using Pearson correlation in SPSS. The results indicate a significant positive relationship between attendance and learning outcomes, with a Pearson correlation of 0.885 and a coefficient of determination (R²) of 78.3%. Besides attendance, factors such as motivation, teaching quality, and family and environmental support also influence learning outcomes. Therefore, improving student attendance through engaging teaching strategies and collaborative support is essential for optimizing mathematics achievement.